The effect of public employment on children's work and school attendance: Evidence from a social protection program in Argentina - Randall Juras (IZA Journal of Labor & Development, 2014)
I assess the short-term impact of a public employment program on child labor and school attendance in Argentina. Public employment increases opportunities for adults outside the household, and may correspondingly raise the returns to children's productive activities at home. The effect of public employment on school attendance may thus be small. However, I find that the program substantially increased children's school attendance in addition to reducing child labor. My empirical strategy exploits an arbitrary enrollment cutoff date to compare program beneficiaries with a propensity-matched group of applicants not receiving benefits.
Keywords: J22; J13; J68; O15; 330; Child labor; Public employment; Social protection; Argentina